Analysis of Crustal Stress and Its Influence on the Stability of the Deep Tunnel in the Huanaote Mining Area - Mingde Zhu; Yantian Yin; Chao Peng; Li Cheng; Yingjie Hao; Kuikui Hou; Haoqin Zhang; Jie Zhang (Advances in Civil Engineering)
Crustal stress is a critical parameter utilized to analyze the stability of the tunnel in underground hard-rock mining sites. In order to analyze the distribution law of crustal stress and its influence on the stability of the deep tunnel in the Huanaote mining area, the in-situ stress field model of this area was constructed firstly by using the borehole stress relief method. Moreover, the numerical model is established based on three real engineering conditions: the excavation direction is parallel, vertical, and intersection to the measured maximum horizontal principal stress direction, respectively. Results show that, compared with the other two layout schemes, the stress of two side walls reaches peak at 27 MPa, when the excavation direction is intersected to the measured maximum horizontal principal stress direction, which indicates that the support and maintenance of two side walls should be strengthened to ensure the stability of the tunnel and the safety of personnel and equipment in real projects.